2019
DOI: 10.1096/fj.201902265r
|View full text |Cite
|
Sign up to set email alerts
|

Icariin and its phosphorylated derivatives alleviate intestinal epithelial barrier disruption caused by enterotoxigenic Escherichia coli through modulate p38 MAPK in vivo and in vitro

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractThe natural product icariin (ICA) and its phosphorylated derivatives (pICA) have been shown to have outstanding anti-inflammatory and antioxidant properties. This study was to explore the protective effects of ICA and pICA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 48 publications
2
28
0
1
Order By: Relevance
“…It combines with the microvilli of intestinal epithelial cells and with receptors on the surface of cells through various types of fimbriae adhesins; then, it propagates in large numbers, which releases enterotoxin, a protein that induces diarrhea [3]. Studies con-ducted on piglet intestinal epithelial cells have shown that ETEC K88-activated oxidative stress destroys the intestinal epithelial barrier and increases permeability, which eventually leads to diarrhea [4]. In addition to piglets, ETEC K88 can activate oxidative stress in mice [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It combines with the microvilli of intestinal epithelial cells and with receptors on the surface of cells through various types of fimbriae adhesins; then, it propagates in large numbers, which releases enterotoxin, a protein that induces diarrhea [3]. Studies con-ducted on piglet intestinal epithelial cells have shown that ETEC K88-activated oxidative stress destroys the intestinal epithelial barrier and increases permeability, which eventually leads to diarrhea [4]. In addition to piglets, ETEC K88 can activate oxidative stress in mice [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that ICA can significantly alleviate intestinal injury induced by LPS, suggesting that ICA may have an outstanding protective effect on intestinal epithelium. 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“…Our data exhibited that 3OC12 and 3OC14 can induce a loss of mitochondrial membrane potential in intestinal epithelial cells and severe apoptosis. There is an evidence that the activation of oxidative stress is strongly associated with the development of intestinal epithelial barrier dysfunction, primarily due to the ability of oxidative stress to disrupt TJs (Xiong et al, 2020). In the present study, we employed NAC, a powerful antioxidant, to investigate the potential mechanism by which QS autoinducer disrupt the intestinal epithelial barrier.…”
Section: Discussionmentioning
confidence: 99%